Perception of ethics in the Icelandic Aviation Sector - Nicolas Jeanne 1991- (2015)
This Master’s thesis deals with perception of ethics in the Icelandic aviation sector. It offers a qualitative study to answer the following central research questions: what is the perception of the ethical environment in the aviation sector of Iceland by its top-managers? To introduce the study, a literature review presents an overview of the concepts of ethics, corruption and bribery as well as culture and corporate social responsibility. A special focus is proposed on the different school of thoughts in ethics as well as the relationship between ethics and the law. The study was qualitative and conducted through nine semi-directive interviews in 2015 of top-managers from five different aviation Icelandic aviation organizations. The results show that the panel has a very universal and rule-based perception of ethics. It pointed out the perception that cultural proximity lowers differences in perception and vice-versa. In addition, the study showed that the participants see very little difference between acting ethically and acting legally. This is explained by the very strong regulatory framework the aviation sector is structured by. Overall, it appears that Icelandic aviation managers feel that their sector operates in a very ethical environment and that the law as well as a strong healthy corporate culture and values are the guardians of this ethical environment.